H antigen presence in an Ascaris lumbricoides extract Presencia de antígeno H en un extracto de Ascaris lumbricoides - Patricia Ponce de León; Patricia Foresto; Juana Valverde (Revista do Instituto de Medicina Tropical de São Paulo, 2005)
Previous experiences have demonstrated the same ABO system and P system antigens in A. lumbricoides extracts and in their hosts. The aim was to show the behavior of an A. lumbricoides extract from an O Group patient against monoclonal antibodies of different specificities. Agglutination Inhibition Tests were carried out facing the extract against monoclonal antibodies (anti A 2.23; anti B 2.54; anti B 2.62; anti AB 2.39 and anti H 2.72) in optimal concentrations. Suspensions of O Group fresh red cells were used as revealing system. The extract only inhibited the agglutination of anti H 2.72 with O erythrocytes. The semiquantitative Agglutination Inhibition Test of the extract was made against two series of anti H 2.72 dilutions by using O Group fresh red cells as revealing system. A difference of five dilutions between the titers of both series has been observed and the presence of H Antigen in the extract has been significantly confirmed. The fact that the extract did not inhibit the agglutination against anti A, anti B and anti AB has corroborated our previous observations about absence of A and B epitopes in A. lumbricoides extracts from O Group patients. The results of the preceding studies and this experience have demonstrated the membrane glycoconjugated importance in A. lumbricoides. They could be involved in molecular mimicry for this parasite. Experiencias previas han demostrado los mismos antígenos del Sistema ABO y del Sistema P en extractos de A. lumbricoides y en sus huéspedes. El objetivo fue mostrar el comportamiento de un extracto de A. lumbricoides de un paciente Grupo O frente a anticuerpos monoclonales de diferentes especificidades. Se hicieron pruebas de Inhibición de la Aglutinación enfrentando el extracto contra anticuerpos monoclonales (anti A 2.23; anti B 2.54; anti B 2.62; anti AB 2.39 y anti H 2.72) en dosis óptimas. El sistema revelador fue una suspensión fresca de eritrocitos Grupo O. El extracto sólo inhibió la aglutinación de anti H 2.72 con eritrocitos O. Se hizo la inhibición de ...